Fatores microbiológicos e imunológicos envolvidos no desenvolvimento da cárie precoce da infância - Colombo, Natália Helena [UNESP] (2015)
Early childhood caries (ECC) is still a serious public health problem worldwide, especially in developing countries. Studies have been suggested the association among frequent intake of fermentable carbohydrates such as sucrose, high cariogenic microorganism's counts and child's immune vulnerability in the etiology of ECC. The objective of this study was to evaluate the microbiological and immunological factors for the development of early childhood caries. 36 to 60 monthold children were selected and distributed into three groups: caries free (CF), ECC and S-ECC (severe-ECC). Questionnaires about socio-economic-cultural data, oral hygiene habits and food-frequency diary were completed by the parents. Saliva and dental biofilm were collected from children and processed for subsequent laboratorial tests. The following analyses were determined: total IgA and IgA response against S. mutans GbpB by ELISA and Western blot, respectively; salivary concentrations of antimicrobial peptides (AMPs): defensins hBD-2 and hBD-3, cathelicidin LL-37 and histatin 5 (HTN-5) by ELISA; salivary detection and quantification of Streptococcus mutans, Streptococcus sobrinus, Lactobacillus spp., Bifidobacterium spp. and Scardovia wiggsiae by qRT-PCR, and these data were correlated with mutans streptococci (MS) and Lactobacillus spp. levels by culture in specific medium. Results showed that S-ECC children had reduced family income compared to ECC and CF. However, sugar intake did not differ among the groups. S-ECC group had higher MS count than CF/ECC groups. Positive correlations between salivary IgA response against GbpB and MS counts were found when the entire population was evaluated. When children with high mutans streptococci counts were compared, S-ECC group showed a significant decrease in IgA antibody levels against GbpB compared...